"n Nuwe psalmomdigting in Afrikaans Uitgangspunte, beleid, probleme - Kloppers, Elsabè (Hervormde teologiese studies, 2000)
A new Metrical Psalter in Afrikaans: Premises, policy, problems. For almost twenty years a commission of the Afrikaans-speaking Dutch Reformed churches has been working on a new metrical Psalter. The policy of versifying the Biblical texts is rigid and in many instances theologically outdated. The primary problems are the principle of a reproductive versification, a versification in one form and style, the lack of a hermeneutical approach, the question whether all 150 Psalms need to be reproduced anew and the lack of a proper liturgical function of many of the texts.